New Perspectives in Rehabilitation after Traumatic Brain Injury - Andelic, Nada; Røe, Cecilie; Helseth, Eirik; Howe, Emilie Isager; Forslund, Marit Vindal; Hellstrøm, Torgeir (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
There has been increased focus on evaluating the scientific knowledge base within the field of traumatic brain injury (TBI) rehabilitation. TBI rehabilitation comprises several phases, from acute medical care to post-acute care in rehabilitation facilities and chronic care in the community. Rehabilitation is a multidisciplinary effort that covers the full spectrum of medical neuroscience, cognitive neuroscience, pharmacology, brain imaging, and assistive and smart technology. A future challenge is to integrate these areas to guide TBI rehabilitation into extensive research and clinical practice. The use of smart technologies and improved brain imaging techniques has an important future in the rehabilitation of patients with cognitive difficulties and disabilities. There is also the need for broad international collaboration to establish large multinational clinical trials in order to define effective service provision and to reach a consensus on the best evidence-based practice of TBI rehabilitation. With this Special Issue, we hope to encourage submissions that discuss ongoing knowledge gaps and controversies, and focus on new perspectives regarding the rehabilitation and management of TBI.